Comparative Stability of Two Anti-hyperpigmentation Agents: Kojic Acid as a Natural Metabolite and Its Di-Palmitate Ester, Under Oxidative Stress; Application to Pharmaceutical Formulation Design - Sahar Tazesh; Elnaz Tamizi; Mohammadreza Siahi Shadbad; Nazli Mostaghimi; Farnaz Monajjemzadeh (Tabriz University of Medical Sciences, 2022)
Purpose: Kojic acid (KA) a natural metabolite and its dipalmitate ester, kojic acid dipalmitate(Kadp) are both prescribed to treat skin hyperpigmentation. Stress test reveals the intrinsicstability of active ingredients and leads to selection of the suitable formulations. This researchevaluates the comparative stability of KA and its di-palmitate ester under liquid oxidative stress.Methods: The HPLC-UV/PDA method with a C18 column was utilized. Liquid oxidative stresswas induced using hydrogen peroxide (H2O2). Degradation was separately induced for eachdrug, and they were compared to each other.Results: Kadp degraded more rapidly in similar liquid oxidative stress conditions than KA did.The superior degradation model was the first order for both drugs based on the mean percentageerror (MPE) values, indicating the dependency of the reaction rate on the initial concentrationof the reactive substance. Ring opening was proposed as the most possible theory for KA andKadp oxidative degradation.Conclusion: It is suggested to use KA instead of Kadp in less stable formulations, such asextemporaneous preparations. The incorporation of antioxidant excipients in Kadp formulationsis recommended for yielding better stability results. Formulating Kadp in the internal phase ofo/w emulsion formulations may protect this susceptive molecule from oxidative degradationduring the shelf life of the pharmaceutical preparation. Further studies are required to study theexact mechanism of the degradation process.